Matematyka

Autorzy:Karolina Wej, Wojciech Babiański, Ewa Szmytkiewicz, Jerzy Janowicz

Wydawnictwo:Nowa Era

Rok wydania:2016

Oblicz. a) (4/3)^(-2) ∙(6/7)^(-2) 4.75 gwiazdek na podstawie 8 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

`a) \ \ (4/3)^(-2)*(6/7)^(-2)*(49/8)^(-2)=(4/strike3^1*strike6^2/strike7^1*strike49^7/8)^(-2)=` `(strike8^1*7/strike8^1)^(-2)=7^(-2)=1/49` 

`b) \ \ 4,5^(-3)*(5/18)^(-3)*4^(-3)=(4,5*5/18*4)^(-3)=(4 1/2*5/18*4)^(-3)=(strike9^1/2*5/strike18^2*4)^(-3)=`  

`=(5/strike4^1*strike4^1)^(-3)=5^(-3)=(1/5)^3=1/125` 

`c) \ \ (2/21)^(-3)*15^(-3)*7^(-3)=(2/strike21^3*15*strike7^1)^(-3)=(2/strike3^1*strike15^5)^(-3)=10^(-3)=(1/10)^3=1/1000` 

`d) \ \ 18^(-2):6^(-2)+(-3)^3*(-3)^(-5)=(18:6)^(-2)+(-3)^(3+(-5))=3^(-2)+(-3)^(-2)=` 

`=(1/3)^2+(-1/3)^2=1/9+1/9=2/9` 

`e) \ \ 1,3^(-2):(26/15)^(-2)-(5/9)^(-7)*(1 4/5)^(-7)=` `(1,3:26/15)^(-2)-(5/9*1 4/5)^(-7)=(strike13^1/strike10^2*strike15^3/strike26^2)^(-2)-(strike5^1/strike9^1*strike9^1/strike5^1)^(-7)=` 

`=(3/4)^(-2)-1^(-7)=(4/3)^2-1=16/9-1=1 7/9-1=7/9` 

`f) \ \ 0,4^3*(5/16)^3:4^(-3)+4^0=(0,4*5/16)^3:4^(-3)+4^0=(strike4^1/strike10^2*strike5^1/strike16^4)^3:4^(-3)+4^0=` 

 `(1/8)^3:(1/4)^3+4^0=(1/8:1/4)^3+4^0=(1/strike8^2*strike4^1)^3+4^0=(1/2)^3+1=1/8+1=1 1/8`